What Explains Private Saving in Mexico? - Swiston, Andrew (IMF Working Papers; Working Paper, 2006)
This paper examines the factors influencing Mexico's private saving rate. Cross-country analysis finds that Mexico's private saving is somewhat higher than could be explained by its fundamentals, but lower than in the average country in the sample. This analysis suggests that Mexico's greater reliance on external saving, its relatively high population dependency ratio, and its less developed financial system have been the main factors holding back private saving. Time-series analysis finds that movements in private saving have not been associated with similar shifts in investment, as changes in public saving and external saving have tended to offset movements in private saving. This is consistent with the direction of causality being from investment to saving and suggests that policy measures should focus on creating conditions favorable to increased investment.